2002
DOI: 10.1103/physreva.65.042715
|View full text |Cite
|
Sign up to set email alerts
|

Intermanifold similarities in partial photoionization cross sections of helium

Abstract: Using the eigenchannel R-matrix method we calculate partial photoionization cross sections from the ground state of the helium atom for incident photon energies up to the N = 9 manifold. The wide energy range covered by our calculations permits a thorough investigation of general patterns in the cross sections which were first discussed by Menzel and co-workers [Phys. Rev. A 54, 2080]. The existence of these patterns can easily be understood in terms of propensity rules for autoionization. As the photon energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Menzel et al reported on measurements of partial cross sections up to the ionization threshold I 5 employing two spherical-sector-plate electrostatic analyzers [9,10] and discussed the observed general patterns in n . Here, n describes the PCS for the channel leading to He + , with the single electron in a state with principal quantum number n. Very recently, Schneider et al [11] and van der Hart et al [12] confirmed in their calculations these regularities in n up to the ionization threshold I 9 . The similarities in the PCSs for the energy region with a small number of pertubers, also called "general patterns," can be well understood with the so-called propensity rules based on the molecular adiabatic approximation [11].…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Menzel et al reported on measurements of partial cross sections up to the ionization threshold I 5 employing two spherical-sector-plate electrostatic analyzers [9,10] and discussed the observed general patterns in n . Here, n describes the PCS for the channel leading to He + , with the single electron in a state with principal quantum number n. Very recently, Schneider et al [11] and van der Hart et al [12] confirmed in their calculations these regularities in n up to the ionization threshold I 9 . The similarities in the PCSs for the energy region with a small number of pertubers, also called "general patterns," can be well understood with the so-called propensity rules based on the molecular adiabatic approximation [11].…”
Section: Introductionsupporting
confidence: 53%
“…Here, n describes the PCS for the channel leading to He + , with the single electron in a state with principal quantum number n. Very recently, Schneider et al [11] and van der Hart et al [12] confirmed in their calculations these regularities in n up to the ionization threshold I 9 . The similarities in the PCSs for the energy region with a small number of pertubers, also called "general patterns," can be well understood with the so-called propensity rules based on the molecular adiabatic approximation [11]. As the photon energy increases, the structures in the PCS get more and more complicated due to interferences caused by an increasing number of pertubers, and the general patterns begin to dissolve.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Domke et al [9] resolved for the first time the third Rydberg series, 2pnd, below the n = 2 ionization threshold. Theoretically, various methods were developed to deal with doubly excited states of helium, including configurationinteraction (CI) methods [13][14][15], hyperspherical coordinate methods [16][17][18][19][20][21][22][23], close-coupling approximations [24][25][26], R-matrix methods [27][28][29][30][31][32], complex coordinate method [33][34][35][36], Feshbach projection formalism [37][38][39][40], and the diagonalization method [41][42][43][44][45][46][47]. A detailed review was recently performed by Tanner et al [48].…”
Section: Introductionmentioning
confidence: 99%